Is Performance of Fluorine-18-fluorodeoxyglucose Positron Emission Tomography/Computed tomography (CT) or Contrast-enhanced CT Efficient Enough to Guide the Hilar Lymph Node Staging for Patients with Esophageal Squamous Cell Carcinoma? - Chu, Li; Liu, Shuai; Guo, Tiantian; Zou, Liqing; Li, Bin; Ni, Jianjiao; Yang, Xi; Chu, Xiao; Liang, Fei; Li, Yida; Sun, Yuyun; Li, Qiao; et al. (Frontiers in Oncology, 2022)
Introduction We evaluated the diagnostic performance of fluorine-18-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/computed tomography (CT) and contrast-enhanced CT in the detection of hilar lymph node metastasis (LNM) in esophageal squamous cell carcinoma (ESCC) to determine their value in guiding hilar lymph node staging and delineating radiation target volume. Methods Consecutive patients with ESCC who underwent both PET/CT and contrast-enhanced CT before radical lymphadenectomy and esophagectomy at our institution from September 2009 to November 2018 were enrolled. The sensitivity (SE), specificity (SP), positive predictive value (PPV), and negative predictive value (NPV) of FDG-PET/CT and contrast-enhanced CT for diagnosing hilar LNM were calculated. Results Of the 174 patients included, contrast-enhanced CT predicted nine positive cases, while PET/CT predicted one, and eight (4.6%) were identified as pathologically positive for their resected hilar lymph nodes. The SE, SP, PPV, and NPV of PET/CT and contrast-enhanced CT were 0.000, 0.994, 0.000, and 0.954; and 0.125, 0.952, 0.111, and 0.958, respectively. The specificity showed a significant difference (P=0.037). PET/CT is slightly more specific than contrast-enhanced CT. Conclusions PET/CT and contrast-enhanced CT may be useful tools for predicting the negativity of hilar LN status, but they are not recommended for guiding the hilar lymph node staging and the delineating of hilar LNM in radiotherapy planning of ESCC patients based on their low PPV.